2009
DOI: 10.2174/1874428100802010057
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship Between Electrogustometry and Sour Taste Perception

Abstract: Abstract:In a recent study Ellegård, Goldsmith, Hay, and Morton concluded that electrogustometry is neither mediated by sour taste receptors, nor reflects sour taste quality. While aspects of electric taste await a full explanation, such farreaching claims have significant implications for the future of electrogustometry in clinical practice. The current paper presents a critique of the grounds upon which the arguments were based, and suggests that these conclusions may be premature.Ellegård, Goldsmith, Hay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated increased EGM threshold with aging (14,15) or smoking (17) . While some studies favored the electric taste as a gustatory phenomenon (34)(35)(36) , others failed to show a significant correlation between electric and common chemical tastes (37)(38)(39) , signifying the unique nature of electric taste. In addition, electric stimulation may be contaminated by trigeminal activation (40) .…”
Section: Egm Taste Sensitivitymentioning
confidence: 99%
“…Previous studies have demonstrated increased EGM threshold with aging (14,15) or smoking (17) . While some studies favored the electric taste as a gustatory phenomenon (34)(35)(36) , others failed to show a significant correlation between electric and common chemical tastes (37)(38)(39) , signifying the unique nature of electric taste. In addition, electric stimulation may be contaminated by trigeminal activation (40) .…”
Section: Egm Taste Sensitivitymentioning
confidence: 99%